Perioperative management, operative techniques, and pitfalls in the surgical treatment of patients with diffuse idiopathic skeletal hyperostosis: a narrative review - Netanja I. Harlianto; Jonneke S. Kuperus; Jorrit-Jan Verlaan (Exploration of Musculoskeletal Diseases, 2023)
Diffuse idiopathic skeletal hyperostosis (DISH) can lead to dysphagia, airway obstruction, and unstable vertebral fractures. Surgery can be performed to relieve cervical compression or stabilize fractures of the spinal column, with or without decompression of spinal cord injuries. In this review, the peri-operative surgical techniques in cases with DISH are discussed, as well as the pre-operative and post-operative pearls and pitfalls. It is essential for spine surgeons, including orthopedic surgeons and neurosurgeons, to be aware of the considerations, anticipations, and approaches for the management of dysphagia, airway obstruction, and fractures in DISH patients in order to improve patient outcomes for this specific at-risk patient population.